2016
DOI: 10.7904/2068-4738-vii(13)-41
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Rupestris Du Lot Rootstock on Some Technological Traits of Muscat Rusenski and Super Ran Bolgar Table Grape Cultivars

Abstract: Abstract. The choice of rootstock is important not only for the power that it induces on the grafted variety of grapes, but also with respect to its effects on mineral nutrition, content of sugars, total acids and other technological traits. Two table vine varieties-Misket Rusenski and Super ran Bolgar were the objective of the study, grafted on two different SO4 rootstocks (which is widely used in practice and thus accepted control) and Rupestris du Lot (with common name Montikola). A total of 12 technologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…as an example of an organic nitrogen source. R-NH 2 ↔OH -+R-OH+NH 4 + ↔4H + +energy+NO 2 -↔energy+NO 3 -Many studies have shown that only 1.5-3.5% of organic nitrogen in soil is mineralized annually [4]. Even so, this rate of mineralization provides enough mineral nitrogen for normal growth of natural vegetation in most soils except those with low organic matter content, such as desert soils and sandy areas.…”
mentioning
confidence: 99%
“…as an example of an organic nitrogen source. R-NH 2 ↔OH -+R-OH+NH 4 + ↔4H + +energy+NO 2 -↔energy+NO 3 -Many studies have shown that only 1.5-3.5% of organic nitrogen in soil is mineralized annually [4]. Even so, this rate of mineralization provides enough mineral nitrogen for normal growth of natural vegetation in most soils except those with low organic matter content, such as desert soils and sandy areas.…”
mentioning
confidence: 99%